Identification of the Artery of Adamkiewicz Using Multidetector Computed Tomography Angiography (MCTA) - Piola, Flávio P.F.; Nogueira-Barbosa, Marcello H.; Maranho, Daniel A.C.; Martins, Adélson A.; Barbosa, Maurício F. [UNESP]; Herrero, Carlos F.P. Silva (Thieme, 2020)
Objective The aim of the present study is to evaluate the artery of Adamkiewicz by multidetector computed tomography angiography (MCTA) in a Brazilian population. Methods Two independent observers evaluated 86 coronary MCTA examinations. The variables studied included the identification of the artery of Adamkiewicz at its origin level, and its entry side in the spine. Results The artery of Adamkiewicz was detected in 71 (82.5%) examinations. The origin level was identified between the 9th and 11th thoracic vertebrae (T9 and T11) in 56 (79.2%) patients. In 65 (91.5%) patients, the artery was on the left side. The identification of the artery of Adamkiewicz using MCTA showed high reproducibility. Conclusions Our results were consistent with the literature regarding the identification of the artery of Adamkiewicz using MCTA, suggesting that this technique should be considered as an option to recognize this structure. In addition, we found that the distribution of the artery of Adamkiewicz in the Brazilian population is similar to that of other populations, that is, its most common origin is at the left side, between the 8th and 12th thoracic vertebrae (T8-T12).
Keywords: angiography/methods; arteries/pathology; multidetector computed tomography; paraplegia; spinal cord